Double span continuous glulam slabs strengthened with GFRP - Branco, Jorge M. (2014)
Full-scale slab strips were tested in order to analyze the flexural response of GFRP-glulam slab systems under monotonic loading. The type of strengthening technique (externally bonded reinforcement – EBR and near-surface mounted – NSM) and the increase target in terms of ultimate load capacity (20% and 40%) were the main studied parameters. GFRP sheets were utilized in the EBR technique, while GFRP rods were applied in NSM technique. In this work the tests are described in detail, and the obtained results are presented and discussed.